chevron icon chevron icon chevron icon chevron icon

Linear Law

In this article, we will be learning about Linear Law. Specifically, we will be covering the following: 

  • Converting Non-Linear Algebraic Equation into Linear Form
  • Converting Exponential Equation into Linear Form
  • Converting Linear Form of an Equation into Non-Linear Equation

Linear Law

Linear Law Image 1
(i)
Linear Law Image 2
(ii)

When we look at graph (i) above, we see that at the point of turn, there are two possible ways to draw the graph based on the plotted points. However, this leaves a greater room for error as the curve drawn might not be accurate. Hence, a better way to obtain more accurate points is to convert the curve into a straight-line graph.

This is where we will consider Linear Law.

Equation of a Straight Line

Linear Law Image 3

The general equation of a straight line is \(y = mx + c\), where, 

Gradient \(= m\)

y-intercept \(= c\)

Let’s consider another equation, \(\begin{align*} y=m \bigg(\frac{1}{x}\bigg)+c. \end{align*}\)

If we draw the graph of \(y\) against \(x\), we will obtain an exponential graph. However, when the graph of \(y\) against \(\begin{align*} \frac {1}{x} \end{align*}\) is drawn, we will obtain a straight line.

Converting Non-Linear Algebraic Equations into Linear Form

The linear form of any non-linear equation is given by:

\(Y=mX+c\)

where \(m\) is the gradient, \(c\) is the y-intercept, and \(Y\) and \(X\) must contain only \(x\) and \(y\) variables.

Examples

\(\begin{align*} X &= xy \;; &Y &= x^2 &------ &\text{ Acceptable} \\ \\ X &= 2x \;; & Y &= \frac{4}{y} &------ &\text{ Unacceptable} \\ \\ X &= 2^x \;; & Y &= 3^y &------ &\text{ Unacceptable} \\ \\ X &= x^n \;; & Y &= y^n &------ &\text{ Acceptable} \end{align*} \)

 

Non-Linear Equation Linear Form

\(\begin{align*} y = \frac{2}{x}-5 \end{align*}\)

\(\begin{align*} y = \;&2\bigg(\frac{1}{x}\bigg)-5 \\ \\ &\text {where}\\ \\ Y = xy, \;X &= x^2,\; m = 2,\; c = 3 \end{align*} \)

\(\begin{align*} xy=2x^2+3 \end{align*}\)

\(\begin{align*} xy &=2x^2+3 \\ \\ &\text {where} \\ \\ Y = xy, \;X &= x^2, \;m = 2, \;c = 3 \end{align*}\)

 

Question 1:

Complete the table by converting the following equation into linear form \(Y = mX + c\).

Solution:

Non-Linear Equation 

Linear Form

Y

X

m

c

\(\begin{align*} y=2x^3-x^2 \end{align*}\)

\(\begin{align*} y &= 2x^3-x^2 \\ y+x^2 &= 2x^3-x^2+x^2 \\ y+x^2 &= 2x^3 \end{align*} \)

\(y+x^2\)

\(x^3\)

\(2\) \(0\)
\(\begin{align*} y=2x^3-x^2 \end{align*}\)

\(\begin{align*} y &= 2x^3-x^2 \\ y \div x^2 &= (2x^3-x^2) \div x^2 \\ \frac {y}{x^2} &= 2x - 1 \end{align*}\)

\(\begin{align*} \frac {y}{x^2} \end{align*}\) \(x\) \(2\) \(-1\)

\(\begin{align*} y=3x^2 + \frac{4}{x^3} \end{align*}\)

\(\begin{align*} y &=3x^2 + \frac{4}{x^3} \\ y \times x^3 &= \bigg(3x^2 + \frac{4}{x^3}\bigg) \times x^3 \\ yx^3 &= 3x^5 + 4 \end{align*}\)

\(yx^3\) \(x^5\) \(3\) \(4\)

 

Question 2:

Convert the following equation into linear form \(Y = mX + c\).

Solution:

The first operation would be to multiply \((2x + 3)\) on both sides.

\(\begin{align*} (2x + 3) \times y &= \frac {x^5}{2x+3} \times (2x + 3) \\ \\ (2x + 3)y &= x^5 \end{align*} \)

The second operation would be to divide by \(y\) on both sides.

\(\begin{align*} 2x + 3 &= \frac {x^5}{y} \end{align*}\)

Hence, \(\begin{align*} Y = \frac {x^5}{y}, \;X = x,  \;m = 2, \;c = 3 \end{align*}\).

Product, Quotient and Power Laws of Logarithms

\(\begin{align*} log_ax + log_ay &= log_a(xy) \\ \\ log_ax - log_ay &= log_a\bigg(\frac{x}{y}\bigg) \\ \\ log_ax^r &= rlog_ax \end{align*}\)

Converting Exponential Equations into Linear Form

For example, by taking ln on both sides:

Exponential Equation 

Linear Form

\(\displaystyle{ y=ae^{bx}}\)

\(\begin{align*} ln \;y &= ln \;ae^{bx} \\ ln \;y &= ln \;a +ln \;e^{bx} \\ ln \;y &= ln \;a +ln \;e^{bx} \\ ln \;y &= ln \;a +bx\; ln \;e \\ ln \;y &= bx+ln \;a \\ Y = ln \;y&, \;X = x, \;m = b, \;c = ln \;a \end{align*}\)

 

Question 3:

Convert the following equations into linear form \(\begin{align*} Y = mX + c \end{align*}\):

  1. \(\displaystyle{y = 2^{3x}}\)
  2. \(\displaystyle{y^x = 5e^{–3x}}\)
  3. \(\displaystyle{y = x^2 + e^x}\)

Solution:

  1. For the equation \(\begin{align*} y = 2^{3x} \end{align*}\)

\(\begin{align*} ln \;y &=ln \;2^{3x} \\ \\ ln \;y &=3x \;ln \;2 \\ \\ ln \;y &=(3 \;ln \;2)x \end{align*}\)

Therefore, \(\begin{align*} Y = ln \;y, \;X = x, \;m = 3\;ln \;2, \;c = 0. \end{align*} \)

 

  1. For the equation \(\displaystyle{y^x = 5e^{–3x}}\),

\(\begin{align*} ln \;y^x &= ln \;5 \;e^{-3x} \\ \\ ln \;y^x &= ln \;5\;+\;ln \;e^{-3x} \\ \\ x \;ln \;y &= ln \;5\;+\;(-3x)ln \;e \\ \\ x \;ln \;y &= ln \;5-3x \end{align*}\)

Therefore, \(\begin{align*} Y = x \;ln \;y, \;X = x, \;m = −3, \;c = ln \;5. \end{align*}\)

 

  1. For the equation \(\begin{align*} y = x^2 + e^x \end{align*}\),

\(\begin{align*} ln \;(\;y\;-\;x^2\;) &= ln \;e^x \\ \\ ln \;(\;y\;-\;x^2\;) &= x \;ln \;e \\ \\ ln \;(\;y\;-\;x^2\;) &=x \end{align*} \)

Therefore, \(\begin{align*} Y = ln \;(y - x^2), \;X = x, \;m = 1, \;c = 0 \end{align*}\)

Conclusion

In this article, we have learnt of the significance of converting non-linear equations in linear form. More specifically, we have learnt how to convert a non-linear algebraic equation and an exponential equation into linear form \(y = mx + c.\)

Be careful when manipulating a non-linear equation algebraically! For exponential equations, make sure the laws of logarithm are applied correctly to minimise errors.

A last important reminder is that \(Y\) and \(X\) should only contain \(x\) and \(y\) variables, while \(m\) and \(c\) should not contain any \(x\) or \(y\) variables. If this condition is not met, try converting the non-linear equation into a different linear form.

Keep learning! Keep improving!

 

Continue Learning
Quadratic Functions in Real-World Context Equations and Inequalities
Logarithmic Functions Surds
Polynomials & Cubic Equations Partial Fraction
Exponential Functions Coordinate Geometry (Circles)
Linear Law Binomial Theorem

 

Resources - Academic Topics
icon expand icon collapse Primary
icon expand icon collapse Secondary
icon expand icon collapse
Book a free product demo
Suitable for primary & secondary
select dropdown icon
Our Education Consultants will get in touch with you to offer your child a complimentary Strength Analysis.
Book a free product demo
Suitable for primary & secondary
icon close
Default Wrong Input
Get instant access to
our educational content
Start practising and learning.
No Error
arrow down arrow down
No Error
*By submitting your phone number, we have
your permission to contact you regarding
Geniebook. See our Privacy Policy.
Success
Let’s get learning!
Download our educational
resources now.
icon close
Error
Error
Oops! Something went wrong.
Let’s refresh the page!
Geniebook CTA Illustration Geniebook CTA Illustration
Turn your child's weaknesses into strengths
Geniebook CTA Illustration Geniebook CTA Illustration
close icon
close icon
Turn your child's weaknesses into strengths
Trusted by over 220,000 students.
 
Arrow Down Arrow Down
 
Error
Oops! Something went wrong.
Let’s refresh the page!
Error
Oops! Something went wrong.
Let’s refresh the page!
We got your request!
A consultant will be contacting you in the next few days to schedule a demo!
*By submitting your phone number, we have your permission to contact you regarding Geniebook. See our Privacy Policy.